2016
DOI: 10.3109/23337931.2015.1129908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cements on fracture resistance of monolithic zirconia crowns

Abstract: Objectives The present study investigated the effect of cements on fracture resistance of monolithic zirconia crowns in relation to their compressive strength. Materials and methods Four different cements were tested: zinc phosphate cement (ZPC), glass-ionomer cement (GIC), self-adhesive resin-based cement (SRC) and resin-based cement (RC). RC was used in both dual cure mode (RC-D) and chemical cure mode (RC-C). First, the compressive strength of each cement was tested according to a standard (ISO 9917-1:2004)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
58
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 31 publications
10
58
1
3
Order By: Relevance
“…The observation that the cement material did not influence fracture load of both crown materials, LS 2 and ZrO 2 , is in accordance with previous studies (Nakamura et al., ; Weyhrauch, Igiel, Scheller, Weibrich & Lehmann, ). Weyhrauch et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observation that the cement material did not influence fracture load of both crown materials, LS 2 and ZrO 2 , is in accordance with previous studies (Nakamura et al., ; Weyhrauch, Igiel, Scheller, Weibrich & Lehmann, ). Weyhrauch et al.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, fracture load was lower for LS 2 than for ZrO 2 crowns and was not influenced by the cementation technique or the cementation material, confirming previous findings for ZrO s (Nakamura et al., ; Rohr, Märtin & Fischer, ; Stawarczyk et al., ). As both ceramic materials, LS 2 and ZrO 2 , have different compositions and mechanical properties, higher fracture load values were expected for ZrO 2 restorations (Denry & Kelly, ; Nakamura et al., ; Piconi & Maccauro, ).…”
Section: Discussionsupporting
confidence: 90%
“…VE and VM do not offer the option of conventional cementation. The fracture load of oxide ceramics (AL, YZ) is not influenced by the cement due to the high intrinsic strength of the material confirming previous findings for YZ 13,19) . Fracture analysis revealed for cemented crowns an initial fracture start from the loading point.…”
Section: Influence Of the Cement On The Fracture Loadsupporting
confidence: 85%
“…Different types of cement may affect the marginal seal as they differ based on their polymerization shrinkage, hygroscopic expansion, coefficient of thermal expansion, bond with tooth structure, and bond with zirconia . One of the clinical advantages of zirconia crowns is that they may be conventionally cemented with resin‐modified glass ionomer (RMGI) cement or adhesively bonded with resin cement without affecting the strength of the restoration . A 2013 survey by Clinician's Report found that 55% of dentists use RMGI cement and 39% of dentists use a resin cement for zirconia crowns .…”
Section: Introductionmentioning
confidence: 99%